The Gambia : 2002 Article IV Consultation, Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Use of HIPC Interim Assistance-Staff Report; Staff Statement; Public Information Notice, News Brief, and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2004)
The Gambia showed good economic performance under the Poverty Reduction and Growth Facility (PRGF) Arrangement. Executive Directors commended the reforms in the financial sector, the substantial reduction and rationalization of external tariffs, and the settlement of the property dispute with Alimenta, and stressed the need for a tightened monetary policy stance. They welcomed the new PRGF program, which aims at improving fiscal discipline, ensuring good governance, implementing structural and financial reforms, and reducing poverty. They approved for The Gambia a three-year Arrangement under the PRGF, and use of interim assistance.